Social and Cultural determinants of Brain health in Pakistan - Yusra Sellal; Mohammad Wasay (Journal of the Pakistan Medical Association, 2025)
Brain health encompasses the optimal functioning of thebrain throughout life, enabling overall physical, mental,social, and spiritual well-being. Brain health is importantas it ensures individuals to live a content, meaningful lifeand can contribute to society for its social and economicgrowth. Neurologic disorders are a major liability with alifetime prevalence of around 40% worldwide. It isimportant to have an estimate of the neurologic diseaseburden in a country to understand how crippling it can befor individuals, people, and a nation. We analysed thecauses of growing neurologic disease burden by studyingthe social, cultural, and spiritual determinants of brainhealth and how to address health disparities and promoteequitable care. Socioeconomic status influenced by one’seducation, income and job has a positive correlation withhealthcare access. Impoverished countries with a majoritypopulation living under lower socioeconomiccircumstances suffer far more from Neurologic diseasesdue to limited access to healthcare, stress, and generalneglect to health. Urban dwellers have greater access tosub-specialised doctors and imaging equipment, as wellas easier access to medications. As a result, the neurologicdisease burden may be more concentrated inindustrialised cities due to greater recorded data andgreater life expectancy with stroke and epilepsy due tobetter care than in impoverished regions of the country.Spirituality is an important aspect that should beconsidered when treating patients with terminal orchronic illness as it gives individual strength and purposeto face their ailments and be more accepting towardstheir disease outcome. Continues...